(untitled) (Revista Electrónica REDINE, 2018)
Currently educational organizations require people with the ability to exercise the leadership of successfully, what warrants the knowledge of their new styles and the best way to exercise it. that is the reason why, the current study had as main objective to know from the creativity perspective, the leadership on the third millennium scholar organization and exploring the different tendencies that should orientate the changes, in such o way to bring about an efficacious, innovator, and self-managed development. By means of a documental research, where the critical analysis of literature was done, the creativity and leadership were discussed as necessary elements for the third millennium education. In short, the leader is that who dares be creative and encourage a change in the seek of new ways to transform and better a situation, likewise, he focuses on the future as well as settles his energy or to a positive change with a proactive and optimist attitude.